Integrating Landsat-based irrigation mapping and actual evapotranspiration estimates with hydrological modelling to assess regional irrigation dynamics in a large basin experiencing extreme climate variability: Towards a national operational irrigation water accounting system - Jorge L. Peña-Arancibia; Yingying Yu; Tim R. McVicar; Thomas G. Van Niel; Francis H.S. Chiew; Darin Hodgson; Jamie Vleeshouwer; Aarond Dino; Zachary Brown; Anthony Nadelko (Remote Sensing of Environment, 2026)

Wind Is a Primary Driver of Fungal Dispersal Across a Mainland‐Island System - D. Naranjo‐Orrico; O. Ovaskainen; B. Furneaux; J. Purhonen; P. A. Arancibia; S. Burg; N. Moser; J. Niku; G. Tikhonov; E. Zakharov; N. Monkhouse; N. Abrego (Molecular Ecology, 2025)
Dispersal is one of the main processes shaping ecological communities. Yet, for species‐rich communities in natural systems, the role of dispersal in community assembly remains relatively less studied compared to other processes. This is the case for fungal communities, for which predictable knowledge about where and how the dispersal propagules move across space is largely lacking. We sampled fungal communities at their dispersal stage in a lake mainland‐island system in Finland, using a regular grid of 18 × 18 km, including sites on the mainland, islands and over the water. Fungal communities were screened by applying DNA barcoding to air samples. To assess the factors determining fungal dispersal, we modelled aerial fungal communities with a joint species distribution model, including spore traits, weather‐related predictors, and spatial predictors. We found that the probability of occurrence of most species (and consequently species richness measured as the number of OTUs per sample) was lower in low‐connectivity sites (water and isolated islands) compared to high‐connectivity sites (mainland). There was a strong phylogenetic signal in how the fungal species responded to connectivity, indicating that some taxonomic groups are more dispersal limited than others, although such responses were not structured by their trophic guilds. Furthermore, wind speed influenced how species with different spore sizes responded to connectivity: in low‐connectivity sites, species with large sexual spores were detected especially when wind was high, whereas, in high‐connectivity sites, they were detected especially when wind was low. This study demonstrates that air fungal dispersal might be more predictable than previously considered and contributes to the mechanistic understanding of fungal air dispersal.

Potential of mesenchymal stromal/stem cells and spermatogonial stem cells for survival and colonization in bull recipient testes after allogenic transplantation - Moisés N. Segunda; Jahaira Cortez; Carlos Díaz; Richard Arancibia; Cristian G. Torres; Víctor H. Parraguez; Mónica De los Reyes; Oscar A. Peralta (Theriogenology, 2024)

Sodic-calcic alteration and transpressional shear along the Atacama fault system during IOCG mineralization, Copiapó, Chile - N. M. Seymour; J. S. Singleton; R. Gomila; G. Arancibia; J. Ridley; M. L. Gevedon; D. F. Stockli; S. M. Seman (Mineralium Deposita, 2024)
The Punta del Cobre district near Copiapó is a center of iron oxide-copper–gold (IOCG) mineralization spatially and temporally associated with regional sodic-calcic hydrothermal alteration, the Atacama fault system (AFS), and two phases of Early Cretaceous magmatism. Here, we investigate the spatiotemporal and geochemical relationships between magmatism, ductile deformation, and hydrothermal alteration along the ~ 200 to 300-m-thick steeply NW-dipping Sierra Chicharra shear zone, interpreted to be the major strand of the AFS. Mylonitic fabrics and oblique sinistral-reverse kinematic indicators together record coaxial flattening in a transpressional regime. Deformation on the AFS took place before, during, and after intrusion of the synkinematic Sierra Chicharra quartz diorite of the Coastal Cordillera arc at ~ 122 Ma and terminated before intrusion of the unstrained ~ 114 Ma Sierra Atacama diorite of the Copiapó batholith. Geochemical data show that the Copiapó batholith was more mafic and more K-rich than the calc-alkaline Coastal Cordillera arc. This time period thus overlaps IOCG mineralization in the Punta del Cobre district (~ 120 to 110 Ma). Multiple phases of sodic-calcic alteration in and around the AFS shear zone are recognized. Textures of altered rock in the shear zone show both synkinematic assemblages and post-kinematic hydrothermal oligoclase. A ~ 775-m-long andradite vein that cuts the shear zone formed broadly at the end of magmatism in the district (~ 95 Ma). Oxygen isotope ratios from the vein indicate that hydrothermal fluids were likely magmatically derived. Together, this work shows the AFS-related shear zone and nearby IOCG mineralization developed in a regional transpressional regime produced by SE-directed oblique convergence across a NE-striking shear zone. IOCG-related magmatic-hydrothermal fluids exploited this transcrustal shear zone to produce multiple episodes of regional sodic-calcic alteration formed from fluids exsolved from magmas or driven by the heat of the Coastal Cordillera arc and Copiapó batholith.

Tectono-metallogenetic evolution of the Fe–Cu deposit of Dominga, northern Chile - E. Veloso; J. Cembrano; G. Arancibia; G. Heuser; S. Neira; A. Siña; I. Garrido; P. Vermeesch; D. Selby (Mineralium Deposita, 2017)

Partial Characterization of Proteins from Mussel Mytilus galloprovincialis as a Biomarker of Contamination - S. Gorinstein; S.-T. Jung; S. Moncheva; P. Arancibia-Avila; Y.-S. Park; S.-G. Kang; I. Goshev; S. Trakhtenberg; J. Namiesnik (Archives of Environmental Contamination and Toxicology, 2005)

Partial Characterization of Proteins from Mussel Mytilus galloprovincialis as a Biomarker of Contamination - S. Gorinstein; S.-T Jung; S. Moncheva; P. Arancibia-Avila; Y.-S Park; S.-G Kang; I. Goshev; S. Trakhtenberg; J. Namiesnik (Archives of Environmental Contamination and Toxicology, 2005)

Influence of 5-chloro and 5-methyl benzotriazole on the corrosion of copper in acid solution: an experimental and a theoretical approach - A. Arancibia; J. Henriquez-Roman; M. A. Páez; L. Padilla-Campos; J. H. Zagal; J. Costamagna; G. Cárdenas-Jirón (Biotechnology Letters, 2005)

Gastric evacuation of the redspotted catshark under laboratory conditions - G. Aedo; H. Arancibia (Journal of Fish Biology, 2001)
An exponential model provided the best description of the gastric evacuation of the redspotted catshark Schroederichthys chilensis and predicted that 98% of a single initial meal was evacuated in 73·9 h at 16·3°C, slower than that reported for other elasmobranchs.